IMPROVING THE STUDENTS’ READING COMPREHENSION THROUGH REQUEST (RECIPROCAL QUESTION) STRATEGY FOR INDONESIAN JUNIOR HIGH SCHOOL - Rida Fahas (STAIN Sultan Abdurrahman Kepulauan Riau, 2021)
This research is aim at improving to the reading comprehension of eight grade students at SMPN 2 Kedunggalar through Request (Reciprocal Question). In conducting this study, the researcher applied Classroom Action Research (CAR) as the strategy of the research. It was conducted in two cycles and each cycle consisted four phases : planning, acting, observing and reflecting. The subjects of the study were 31 students of class VIII B of SMPN 2 Kedunggalar. There were two forms of data in this study. The qualitative data were obtained by doing observing. Meanwhile, the quantitative data were obtained from the students? reading comprehension score of the pre-test and post-test and they were analyzed by using descriptive. The students have to reach four indicators they are understanding of content, generic structure, languages feature and purpose recount text. Applied request strategy can improved the students reading skill. The enrichment supported them comprehending the texts. The improvement was supported by the compare of the students? mean score from the pre-test, post test 1 and post-test 2 with percentage students passed KKM, 33 percentage 0%,41 percentage 9,7% and 77 96,8%. Their involvement in the reading class also improved. In addition, the students became more active and they enjoyed the process of teaching and learning reading.